Composition of physiologically important fatty acids in great tits differs between urban and rural populations on a seasonal basis - Andersson, Martin N.; Wang, Hong-Lei; Nord, Andreas; Salmon, Pablo; Isaksson, Caroline (Frontiers in Ecology and Evolution, 2015)
Fatty acids (FA) have crucial functions in animals, affecting e.g. inflammatory responses, thermoregulation, and cell membrane fluidity. Diet and ambient temperature affect animals’ FA composition, which, in turn, may influence these physiological processes. Great tits (Parus major) −common in both urban and rural habitats− are mainly granivorous during winter and insectivorous during summer. These diets show pronounced differences in FA composition. Such variation has context-dependent effects on physiology, because the thermal environment, food availability, and levels of pro-inflammatory environmental stressors differ between urban and rural areas. Thus, we investigated how great tit plasma FA composition varied between urban and rural habitats and across seasons. Eight FAs differed between urban and rural birds. Among these, arachidonic acid (omega (ω)-6 polyunsaturated FA) with thermoregulatory and pro-inflammatory properties was more abundant in urban than rural birds in winter, whereas ω-3 FAs with anti-inflammatory properties were more abundant in rural birds. The difference in pro- and anti-inflammatory FAs suggest that the negative health effects that urban birds suffer from being exposed to higher levels of pollutants might be enhanced by an elevated inflammatory response. Eight FAs differed between winter and summer birds. This variation reflected the diet change: FAs common in seeds, e.g. oleic- and linoleic acid, were present in higher amounts in winter birds, whereas ω-3 polyunsaturated FAs that are common in caterpillars were more abundant in summer birds. Overall, a larger seasonal variation was seen among the urban birds. This study is the first to reveal a difference in FA composition between urban and rural populations for all animals studied to date. Future experiments should unravel the physiological implications of this variation, and ultimately, link its effects to fitness of animals with different physiological and dietary requirements in ur